Management of Overweight during Childhood: A Focus Group Study on Health Professionals' Experiences in General Practice. (6th July 2015) - Larsen, Lone Marie; Ledderer, Loni; Jarbøl, Dorte Ejg
Abstract : Background . Because of the increasing prevalence of overweight and obesity in childhood in the Western world, focus on the management in general practice has also increased. Objective . To explore the experiences of general practitioners (GPs) and practice nurses participating in a randomised controlled trial (RCT) comparing two management programmes in general practice for children who are overweight or obese. Methods . Three focus groups with GPs and nurses participating in the RCT. Transcribed data were analysed using systematic text condensation followed by thematic analysis. Results . Health professionals considered it their responsibility to offer a management programme to overweight children. They recognised that management of overweight during childhood was a complex task that required an evidence-based strategy with the possibility of supervision. Health professionals experienced a barrier to addressing overweight in children. However, increasing awareness of obesity in childhood and its consequences in society was considered helpful to reach an understanding of the articulations concerning how best to address the issue. Conclusions . Health professionals in general practice recognised that they have a special obligation, capacity, and role in the management of obesity in childhood. Implementation of future management programmes must address existing barriers beyond an evidence-based standardised strategy.